Clearance of Immunodeficiency-associated Vaccine-derived Poliovirus Infection With Pocapavir. Issue 5 (May 2020) - Copelyn, Julie; Hincks, Jeffrey R.; Wilmshurst, Jo M.; Petersen, Wonita; Howard, Wayne; Jallow, Sabelle; Moonsamy, Shelina; Seakamela, Lerato; Suchard, Melinda; Collett, Marc S.; Eley, Brian
Abstract : Pocapavir exhibits antiviral activity against both polio and nonpolio enteroviruses. There is limited experience of the use of this investigational drug in young children with enteroviral infection. We describe the successful clearance of prolonged immunodeficiency-associated vaccine-derived type 3 poliovirus infection by pocapavir in an infant with underlying X-linked agammaglobulinemia.